(untitled) (Istituto Lombardo - Accademia di Scienze e Lettere • Rendiconti di Lettere, 2019)
The note aims at highlighting the main aspects of the personality of Ezio Vanoni as a politician engaged to translate his scholarly experiences into government action, and particularly to design and support the tax reform known by his name. Social sensitivity, realism, rigor and therefore maximum attention to the organizational aspects of public institutions are essential features of his personality, and inspire his work as a politician, as well as a Catholic thinker and economic planner.